Generation and Detection of Structured Light: A Review - Wang, Jian; Liang, Yize (Frontiers in Physics, 2021)
Structured light beams have rapidly advanced over the past few years, from specific spatial-transverse/longitudinal structure to tailored spatiotemporal structure. Such beams with diverse spatial structures or spatiotemporal structures have brought various breakthroughs to many fields including optical communications, optical sensing, micromanipulation, quantum information processing and super-resolution imaging. Thus, plenty of methods have been proposed and lots of devices have been manufactured to generate structured light beams by tailoring the structures of beams in the space domain and the space time domain. In this paper, we firstly give a brief introduction of different types of structured light. Then, we review the recent research progress in generation and detection of structured light on different platforms such as free space, optical fiber and integrated devices. Finally, challenges and perspectives are also discussed.